Hybrid photonic circuit for multiplexed heralded single photons. Issue 3 (27th March 2014) - Meany, Thomas; Ngah, Lutfi A.; Collins, Matthew J.; Clark, Alex S.; Williams, Robert J.; Eggleton, Benjamin J.; Steel, M. J.; Withford, Michael J.; Alibart, Olivier; Tanzilli, Sébastien
<x xml:space="preserve">Abstract</x> This letter presents a heralded single photon source based on a hybrid technology approach, combining high efficiency periodically poled lithium niobate waveguides, low‐loss laser inscribed circuits, and fast (>1 MHz) fibre coupled electro‐optic switches. Hybrid interfacing different platforms is a promising route to exploiting the advantages of existing technology and has permitted the demonstration of the multiplexing of four identical sources of single photons to one output. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>